Response to loading in ex vivo bovine bone - Khalid, Kamarul Ariffin; Ormsby, Renee T; Welldon, Katie J; Lim, Hui-Peng; Sanusi, Syazwani; Sallehudin, Fatin Nabilah; Atkins, Gerald J; Findlay, David M (2011)
Aims: The response of bone in vivo towards mechanical loading is widely reported1. However, mechanotransduction studies performed in vitro cannot measure biomechanical parameters in real-time or emulate the 3D structure of bone matrix. The Zetos™ system2 is able to overcome the above limitations. Prior studies have investigated the effects of loading ex vivo bone with intact marrow3-5. The aim of this study was to investigate the effect of mechanical loading on ex vivo trabecular bone without marrow. Methods: Trabecular bone cores (10 x 5 mm) were prepared from a fresh 9-month old steer sternum. Care was taken to maintain sterility and viability at all times. Half of 24 bone cores had their marrow removed. Using custom-made bone culture chambers, they were perfused with culture media (7ml/hr) at 37°C. Three treatment groups of eight samples (four with marrow and four without) were either unloaded or mechanically loaded (2,000 μstrain, 1 Hz, 300 cycles daily or 2,000 μstrain, 1 Hz, 100 cycles thrice a day) for 10 consecutive days. Young’s Modulus was measured daily. μCT images before and after the 10 days were taken and analysed. Media was changed daily and its pH measured. Results: Although the initial stiffness and μCT measurements varied widely, despite using a single bone from the same animal, the samples without marrow were more responsive to loading than those with intact marrow. An initial drop in the stiffness of the bone cores was followed by an increase in all treatment groups. Correlation between stiffness and all μCT measurements were superior in samples without marrow. Daily pH measurement indicated increased metabolic activity in the samples. Conclusions: The results suggested that a component of the increase in stiffness was independent of loading. Loading in the physiological range increased stiffness and more so in bone without marrow. Removal of bone marrow is beneficial in terms of uniformity of effect and better correlation between mechanical and structural parameters, perhaps due to better diffusion of growth media.